Práticas obstétricas na assistência ao parto e nascimento em uma maternidade de Belo Horizonte - Ana Maria Magalhaes Sousa (2013)
The process of institutionalization of the childbirth care brought important advances to make the assistance better, on the other side, ge nerated a set of standardized obstetric and interventionist practices, sustaining the technocratic attention model. In response to the unfavorable results of this attention model, from the decade of 1980, arose the movement of humanizing the birth, in addition to welcoming and respectful assistance, proposed assistance based on the scientific evidence. The obstetric practice based on the evidence was described by the OMS e MS, who highlighted the obstetrician nurse in the delivery assistance as a component of humanizing the childbirth, revealing a new organization of the assistance molded on the teamwork. The aim of this study was to analyze the obstetric practices on the assistance of the delivery and birth in a health institution at the city of Belo Horizonte MG, in which nurses and obstetrician doctors develop together this assistance. Methodology: descriptive and exploitative study of transverse design, which included 90 women who have recently given birth and their concepts. Data were collected in medical records with help of statistics packages Epi - Info version 3.5.3 and SPSS 10.0. Results: all 90 wom en who have given birth had only one pregnancy, 67,8% had vaginal birth, in which 87% were assisted by obstetrician nurse s. U seful practices and s hould be encouraged in labor and birth: offering diet (55,6%); freedom of movement and position (94,5%); non - pharmacological method for relieving the pain (79,2%), being shower bath the most used; use of partogram (80%); companion presence (92,2%); early skin contact with the RN (77,5%). Clearly harmful or ineffective practices and that must be eliminated of the labor assistance: use of enema and shaving (0). Improperly practices often used during labor and birth: amniotomy (43,1%), oxytocin infusion (47,7%), analg esia (26,6%), showing statistically significant association with the early admission of women ; episiotomy (11,5%). Clearly harmful or ineffective practices and that must be eliminated of the labor assistance and childbirth: womans position on childbirth lying on back with legs raised (75,4%); Kristeller maneuver (11,5%). Conclusion: practices based on the humanized model were found, but also practices supported on the technocratic model were registered. Even in this institution that incorporates and believes in an assistance realized with humanized practices based on scientific evidences, the transformation of the assistance model on obstetrics is still an actual and urgent challenge which requires efforts from both managers and health professionals.